Investigation of Effective Parameters Ce and Zr in the Synthesis of H-ZSM-5 and SAPO-34 on the Production of Light Olefins from Naphtha - Omer Dhia Aldeen Salah Aldeen; Mustafa Z. Mahmoud; Hasan Sh. Majdi; Dhameer A. Mutlak; Khusniddin Fakhriddinovich Uktamov; Ehsan kianfar (Advances in Materials Science and Engineering)
In this paper, Ce and Zr modified commercial SAPO-34 and H-ZSM-5 catalysts were synthesized via a wet impregnation method and used as catalysts for the production of light olefins from naphtha. The synthesized catalysts were characterized using SEM, TGA, XRD, BET, and NH3-TPD. Thermal catalytic cracking of parent catalysts (SAPO-34 and H-ZSM-5) and modified catalysts with Ce and Zr on the production of light olefins from naphtha has been studied. The effects of different loading of Ce (2–8 wt.%), Zr (2–5 wt.%), and different temperatures on the yield of ethylene and propylene were also investigated. The yield of ethylene and propylene improved by 21.78 wt% and 23.8 wt%, respectively, over 2% Ce and 2% Zr on SAPO-34 catalyst. This is due to the higher acid sites on the surface of modified catalysts. It was found that H-ZSM-5 with 2% Zr loading has the highest yield of light olefins (40.4%) at 650°C in comparison with unmodified parent catalysts, while Ce loading has less effect on the olefin yield compared to Zr loading. Finally, simultaneous loading of Ce and Zr showed no effect on the light olefin yield owing to the significant decline of acid sites.